PENGARUH KUALITAS PELAYANAN, SANKSI PERPAJAKAN, BIAYA KEPATUHAN PAJAK, DAN PENERAPAN E-FILING PADA KEPATUHAN WAJIB PAJAK - Rara Susmita, Putu; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2016)
Tax compliance is the behavior of a taxpayer in doing all tax obligations and use taxation rights with still sticking to the legislation perpajakan. Regarding tax compliance is often the case the last few years is the emergence of non-compliance with taxation. This non-compliance will lead to avoidance and tax evasion that will cause a reduction in tax revenue to the state treasury Indonesia. The purpose of this study was to determine the effect of service quality, tax penalties, tax compliance costs, and the implementation of e-filing in compliance WP OP in East Denpasar. The samples used were 100 respondents to the method of determining the sample was accidental sampling. The data collection techniques questionnaire. data analysis technique used is multiple linear regression analysis. The results obtained by the quality of service, tax penalties, and the implementation of e-filing and significant positive effect on compliance WP OP, whereas tax compliance costs and significant negative effect.
Keywords: tax compliance, quality of care, tax penalties, cost of compliance, e-filing